2019
DOI: 10.1111/rda.13413
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the rainbow trout (Oncorhynchus mykiss) eggs exposed to ionizing radiation during induced androgenesis

Abstract: ContentsIonizing radiation (IR) is applied to inactivate nuclear genome in the salmonid eggs to induce androgenetic development. However, it has been considered that doses of IR used to damage maternal chromosomes may also affect morphology of the eggs and decrease their developmental potential. Thus, the main goal of the present research was to assess alterations in the rainbow trout (Oncorhynchus mykiss) eggs caused by the high dose of IR administered during androgenesis. In the present research, rainbow tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…In C. elegans , as in many species, egg quality and embryogenesis are conditioned by the activity of vitellogenins [ 56 , 61 , 62 , 63 ] and were previously shown to be linked with LD size and their coalescence in the rainbow trout after IR [ 64 ]. In our study we found an increase in LD size and C17Δ decrease with an upregulation of vitellogenins in irradiated worms (SC3).…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans , as in many species, egg quality and embryogenesis are conditioned by the activity of vitellogenins [ 56 , 61 , 62 , 63 ] and were previously shown to be linked with LD size and their coalescence in the rainbow trout after IR [ 64 ]. In our study we found an increase in LD size and C17Δ decrease with an upregulation of vitellogenins in irradiated worms (SC3).…”
Section: Discussionmentioning
confidence: 99%
“…40 min) to the Clinic of Oncology and Radiotherapy, University Clinical Center, Medical University of Gdańsk for irradiation. Irradiation of eggs was performed with a dose of 350 Gy under the same conditions as previously described (Polonis et al 2019). After the treatment, eggs were returned under the same conditions to the hatchery to continue the experiment.…”
Section: Induction Of Androgenesismentioning
confidence: 99%
“…Microsatellite DNA analysis was performed to confirm homozygosity and exclusively paternal inheritance in androgenetic fish. The conditions of DNA extraction and amplification were the same as those described previously (Polonis et al 2019). Three microsatellite markers (loci; OMM: 1107, 1075.…”
Section: Molecular Verification Of Androgenesismentioning
confidence: 99%
See 2 more Smart Citations